The effect of electromyostimulation training on recovery and athlete performance in the sport of volleyball: a review of recent literature - Dedi Iskandar; Herman Subarjah; Yunyun Yudiana; Gilang Ramadan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Electromyostimulation (EMS) training has become a popular method to improve muscle strength and speed up athletes' recovery, especially in the sport of volleyball. However, although many studies support the effectiveness of EMS in individual athletes, its application in volleyball sport, is still not widely researched. Objective: This study aimed to evaluate the effects of EMS on muscle recovery and specific performance in the sport of volleyball. Methodology: The research sought to identify potential benefits and challenges in integrating EMS into volleyball training programmes to maximise overall team performance. The research method involved a comprehensive literature review, with reference to articles published in databases such as PubMed and Scopus. The literature search followed PRISMA guidelines, and only articles relevant to the topic of EMS in volleyball sport were considered. Of the total 220 publications found, only five articles met all inclusion criteria and were further analysed. Results: The results showed that EMS can significantly improve muscle strength and accelerate recovery after intense training, especially in explosive movements such as jumping and change of direction.  Discussion: The study also showed that combining EMS with functional training can improve VO2max capacity, muscle strength and physical endurance. However, the application of EMS in the sport of volleyball requires customisation to ensure that it does not disrupt team dynamics and coordination. Conclusions: EMS has the potential to be an effective tool in improving athlete performance and muscle recovery in volleyball sports. However, further research is needed to understand how EMS can be optimally integrated into team training programmes without disrupting team balance. Future research should also evaluate the long-term impact of EMS on team athlete performance.